LncRNA-mRNA Expression Profiles and Functional Networks Associated with Cognitive Impairment in Folate-deficient Mice - Feng, Xiaojin; Zhan, Fenfang; Hu, Jialing; Hua, Fuzhou; Xu, Guohai (Combinatorial Chemistry & High Throughput Screening, 2022)
Background: Cognitive impairment is a common neurocognitive disorder that affects the health of millions of people worldwide, related to folate deficiency. Objective: The present study aimed to investigate the lncRNA-mRNA functional networks associated with cognitive impairment in folate-deficient mice and elucidate their possible molecular mechanisms. Methods: We downloaded the gene expression profile (GSE148126) of lncRNAs and mRNAs from NCBI Gene Expression Omnibus (GEO) database. Four groups of mouse hippocampi were analyzed, including 4 months (4mo) and 18 months (18mo) of folic acid (FA) deficiency/supplementation. The differentially expressed lncRNAs (DElncRNAs) and mRNAs (DEmRNAs) were identified using gplots and heatmap packages. The functions of the DEmRNAs were evaluated using Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses. The hub genes were identified by CytoHubba plugins of Cytoscape, and protein-protein interaction (PPI) network of deregulated mRNAs was performed using the STRING database. Finally, lncRNA-mRNA co-expression and competitive endogenous RNA (ceRNA) network analyses were constructed. Results: In total, we screened 67 lncRNAs with 211 mRNAs, and 89 lncRNAs with 229 mRNAs were differentially expressed in 4mo_FA and 18mo_FA deficient mice, respectively. GO analyses indicated that DEmRNAs were highly related to terms involved in binding and biological regulation. KEGG pathway analyses demonstrated that these genes were significantly enriched for renin secretion, pancreatic secretion, and AMPK signaling pathways in the 18mo_FA deficiency group. Subsequently, the top 5 hub genes were screened from the PPI network, which may be key genes with the progression of folate deficiency. Upon the lncRNA-mRNA co-expression network analysis, we identified the top 10 lncRNAs having the maximum number of connections with related mRNAs. Finally, a ceRNA network was constructed for DE lncRNAs and DEmRNAs, and several pivotal miRNAs were predicted. Conclusions: This study identified the lncRNA-mRNA expression profiles and functional networks associated with cognitive impairment in folate-deficient mice by bioinformatics analysis, which provided support for the possible mechanisms and therapy for this disease.
Keywords: lncRNA